A method for catalytically preparing polycrystalline diamond

By encapsulating graphite and catalyst in tantalum capsules under high temperature and high pressure conditions, the problem of harsh preparation conditions for polycrystalline diamond in the prior art is solved, and high-quality polycrystalline diamond is prepared at lower pressures and temperatures, avoiding the use of metal binders, reducing costs and improving material performance.

CN116351328BActive Publication Date: 2025-04-29NINGBO UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310307975.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-28
Publication Date
2025-04-29
Estimated Expiration
2043-03-28

AI Technical Summary

Technical Problem

The prior art is difficult to produce high-quality polycrystalline diamonds on a large scale under lower pressure and temperature conditions, and the metal binder added to commercial products reduces the hardness and wear resistance of the material.

Method used

By filling graphite and catalyst into tantalum capsules for high temperature and high pressure synthesis, polycrystalline diamond is prepared under low pressure and temperature conditions by using the catalytic action of the catalyst, avoiding the addition of metal binder.

Benefits of technology

The preparation of high-quality polycrystalline diamonds under lower pressure and temperature conditions is achieved, reducing the production cost, improving the hardness and wear resistance of the material without the need for adding metal binders.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116351328B_ABST
    Figure CN116351328B_ABST
Patent Text Reader

Abstract

The invention discloses a method for catalytically preparing polycrystalline diamond, comprising the following steps: loading graphite and a catalyst into a tantalum capsule for packaging, then pressing the packaged tantalum capsule into a block and loading it into a synthesis cavity for high-temperature and high-pressure synthesis, naturally cooling to room temperature after the synthesis is completed, and obtaining polycrystalline diamond after pressure relief. Compared with the prior art, the invention has the following advantages: the pressure required for preparing polycrystalline diamond in the invention is relatively low, and no metal binder or the like needs to be added, and the polycrystalline diamond is prepared through the catalytic action of the catalyst; the preparation method of the invention greatly reduces the pressure and temperature conditions for converting graphite into polycrystalline diamond, and synthesizes polycrystalline diamond material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polycrystalline diamond preparation, and in particular relates to a method for preparing polycrystalline diamond by catalysis. Background Art

[0002] Diamond has extremely high hardness and is known as the "teeth of industry", but diamond single crystals are prone to break along the 111 plane, forming cleavage planes and are highly brittle. Natural polycrystalline diamond is a polycrystalline aggregate formed by direct transformation of various carbon sources under high temperature and high pressure conditions, and directly bonded by diamond nano or micro grains. In addition to having good thermal stability and wear resistance of diamond, it also usually exhibits a hardness that is usually higher than that of diamond single crystals. At the same time, it has the isotropic characteristics that diamond single crystals do not have, has higher toughness, and has better mechanical properties than diamond single crystals in all aspects. Therefore, it has higher processing accuracy and service life, and has important applications in aerospace, geological exploration, oil extraction, precision machining and other fields. Due to the strong covalency of diamond, the sintering of diamond powder is extremely poor, and the mechanical properties of fired polycrystalline diamond are difficult to exceed those of diamond single crystals themselves. Currently, commercial polycrystalline diamond containing metal binders has isotropic characteristics, but metal binders such as cobalt and nickel greatly reduce the hardness, wear resistance and thermal stability of polycrystalline diamond. High-quality polycrystalline diamond without adding any sintering aids can effectively avoid the disadvantages of the above two diamond materials and has greater application potential.

[0003] At present, the main methods for directly preparing polycrystalline diamond are chemical vapor deposition (CVD) and high temperature and high pressure method (HPHT). The direct preparation method of polycrystalline diamond usually does not require the addition of sintering agents. The performance and cost of polycrystalline diamond prepared by the high temperature and high pressure method are usually lower than those of the chemical vapor deposition method. The precursors for synthesizing polycrystalline diamond under high temperature and high pressure mainly include two types of carbon sources: graphite and non-graphite. Since T. Irifune et al. used polycrystalline graphite to prepare polycrystalline diamond with excellent performance under high temperature and high pressure conditions, people have treated graphite in different ways and selected non-graphite precursors (fullerene, amorphous carbon, glassy carbon and carbon nanotubes, etc.) to prepare polycrystalline diamond to reduce the temperature and pressure conditions of direct conversion. Although nano-carbon sources can reduce the temperature and pressure of preparation to a certain extent, their conversion pressure and temperature are still much higher than industrial production conditions. Therefore, synthesizing polycrystalline diamond with better comprehensive properties (hardness, fracture toughness, thermal stability, etc.) has become a common goal pursued by the superhard material industry. Based on the above, the current large-scale production of polycrystalline diamond faces the problem of harsh synthesis conditions (≥15GPa, 2300-2500℃). At the same time, ultra-high pressure and ultra-high temperature experimental conditions also limit the size of NPD, resulting in the inability to prepare large-sized polycrystalline diamond.

[0004] Therefore, in order to promote the industrialization of polycrystalline diamond, it is urgent to reduce the temperature and pressure range of polycrystalline diamond preparation, so as to achieve the purpose of increasing sample size and reducing preparation cost, and exploring suitable catalysts to reduce preparation conditions is the key to solving the above problems. Therefore, designing new conversion methods to achieve the production of polycrystalline diamond under milder conditions is very important for reducing energy and time barriers and understanding the conversion mechanism of diamond. Summary of the invention

[0005] The purpose of the present invention is to prepare polycrystalline diamond by adding a catalyst under relatively low pressure and without adding a metal binder, thereby greatly reducing the pressure and temperature conditions for converting graphite to polycrystalline diamond and synthesizing polycrystalline diamond materials.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for catalytically preparing polycrystalline diamond, the method comprising the following steps:

[0007] The graphite and the catalyst are encapsulated in a tantalum capsule, and then the encapsulated tantalum capsule is pressed into a block and loaded into a synthesis cavity for high temperature and high pressure synthesis. After the synthesis is completed, it is naturally cooled to room temperature, and polycrystalline diamond is obtained after the pressure is released.

[0008] Preferably, the catalyst is calcium hydroxide. By using calcium hydroxide as a catalyst and utilizing the water catalysis of calcium hydroxide decomposition, polycrystalline diamond can be prepared without adding a metal binder or the like.

[0009] Preferably, the catalyst is ammonia borane. By using ammonia borane as a catalyst, high temperature and pressure conditions are not required, and polycrystalline diamond can be prepared directly under low pressure and temperature conditions through the catalytic effect of hydrogen generated by the decomposition of ammonia borane.

[0010] Preferably, the conditions for the high temperature and high pressure synthesis are as follows: the synthesis pressure is 10 GPa, the synthesis temperature is 1800° C., and the heat and pressure holding time is 10 minutes.

[0011] Preferably, the graphite has a particle size of 1-10 μm.

[0012] Preferably, after the pressed tantalum capsule is loaded into the synthesis cavity, the synthesis cavity is heated by an energized rhenium tube, magnesium oxide is used as the pressure transmission medium, and the tantalum capsule is protected by hexagonal boron nitride, and then high-temperature and high-pressure synthesis is performed. In order to ensure the uniformity of the temperature of the synthesis sample cavity, the heating method adopted in this method is the indirect heating of the energized rhenium tube; in order to ensure that the tantalum capsule does not react with the rhenium tube that generates heat, hexagonal boron nitride is used to protect the packaged sample.

[0013] Preferably, the tantalum capsule obtained after the briquetting is cylindrical.

[0014] Compared with the prior art, the present invention has the following advantages:

[0015] 1. The pressure and temperature required for preparing polycrystalline diamond in the present invention are relatively low, and no metal binder or the like needs to be added. Polycrystalline diamond is prepared through the catalytic action of a catalyst;

[0016] 2. The preparation method of the present invention greatly reduces the pressure and temperature conditions for converting graphite into polycrystalline diamond, and synthesizes polycrystalline diamond. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is a schematic diagram of the assembly of the packaged sample in Example 1;

[0018] Figure 2 is the Raman image of the polycrystalline diamond prepared under the conditions of 10 GPa and 1800°C in Example 1;

[0019] Figure 3 is a schematic diagram of the assembly of the packaged sample in Example 2;

[0020] Figure 4 is the Raman image of polycrystalline diamond prepared under 10 GPa and 1800° C. in Example 2;

[0021] Figure 5 is a schematic diagram of the assembly of the packaged sample in Example 3;

[0022] Figure 6 is the Raman image of the sample prepared at 10 GPa and 1800°C in Example 3;

[0023] Figure 7 is a scanning electron microscope image of the polycrystalline diamond material prepared in Example 1;

[0024] Figure 8 3 is a scanning electron microscope image of the polycrystalline diamond material prepared in Example 2. DETAILED DESCRIPTION

[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0026] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0027] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0028] The embodiment of the present invention provides a method for catalytically preparing polycrystalline diamond, comprising the following steps: encapsulating graphite and a catalyst into a tantalum capsule, then pressing the encapsulated tantalum capsule into a block and then placing it into a synthesis cavity for high-temperature and high-pressure synthesis, naturally cooling to room temperature after the synthesis is completed, and obtaining polycrystalline diamond after decompression.

[0029] In one specific embodiment, the catalyst is calcium hydroxide. By using calcium hydroxide as a catalyst and utilizing the water catalytic effect of calcium hydroxide decomposition, polycrystalline diamond can be prepared without adding a metal binder or the like.

[0030] In one specific embodiment, the catalyst is ammonia borane. By using ammonia borane as a catalyst, high temperature and pressure conditions are not required, and the polycrystalline diamond material is prepared under low pressure and temperature conditions by directly catalyzing the decomposition of ammonia borane to generate hydrogen.

[0031] In the above embodiment, the conditions of high temperature and high pressure synthesis are as follows: the synthesis pressure is 10 GPa, the synthesis temperature is 1800° C., and the heat and pressure holding time is 10 minutes.

[0032] In a specific embodiment, the particle size of graphite is 1-10 μm.

[0033] In a specific embodiment, after the pressed tantalum capsule is loaded into the synthesis cavity, the synthesis cavity is heated by an energized rhenium tube, magnesium oxide is used as a pressure transmission medium, and the tantalum capsule is protected by hexagonal boron nitride, and then high-temperature and high-pressure synthesis is performed. In order to ensure the uniformity of the temperature of the synthesis sample cavity, the heating method used in this method is the indirect heating of the energized rhenium tube; in order to ensure that the tantalum capsule does not react with the rhenium tube that generates heat, hexagonal boron nitride is used to protect the packaged sample.

[0034] In a specific embodiment, the tantalum capsule obtained after briquetting is cylindrical.

[0035] The technical effects of the present invention are described below in conjunction with specific embodiments.

[0036] Example 1

[0037] Graphite (1-10 microns) and ammonia borane interlayers are encapsulated in a tantalum capsule, and the tantalum capsule is formed using a hydraulic press. The sample is placed in a high-pressure synthesis chamber, and the synthesis chamber is heated by an energized rhenium tube. Magnesium oxide is used as a pressure transmission medium, and hexagonal boron nitride is used to protect the chamber. The synthesis pressure is 10GPa, the synthesis temperature is 1800℃, and the heat and pressure holding time is 15 minutes. After stopping the heating, the sample is naturally cooled to room temperature and then the pressure is released. The Raman results of the prepared polycrystalline diamond sample are shown in Figure 2 , Figure 7 This is a scanning electron microscope image of the sample prepared in this example.

[0038] Example 2

[0039] Graphite (1-10 microns) and calcium hydroxide interlayers are encapsulated in a tantalum capsule, and the tantalum capsule is formed using a hydraulic press. The sample is placed in a high-pressure synthesis chamber, and the synthesis chamber is heated by an energized rhenium tube. Magnesium oxide is used as a pressure transmission medium, and hexagonal boron nitride is used to protect the chamber. The synthesis pressure is 10GPa, the synthesis temperature is 1800℃, and the heat and pressure holding time is 15 minutes. After stopping the heating, the sample is naturally cooled to room temperature and then the pressure is released. The Raman results of the prepared diamond sample are shown in Figure 4 , Figure 8 This is a scanning electron microscope image of the sample prepared in this example.

[0040] Example 3

[0041] Graphite (1-10 microns) was encapsulated in a tantalum capsule, and after powder pressing with a hydraulic press, the sample was placed in a high-pressure synthesis cavity. The synthesis cavity was heated by an energized rhenium tube, magnesium oxide was used as the pressure transmission medium, and hexagonal boron nitride was used to protect the cavity. The synthesis pressure was 10GPa, the synthesis temperature was 1800℃, and the heat and pressure holding time was 10 minutes. After stopping the heating, the sample naturally cooled to room temperature and then released the pressure. The Raman results of the prepared sample are shown in Figure 6 .

[0042] The experiments involved in the above embodiments can be completed on a Kawai type 1000t press.

[0043] In the above-mentioned embodiments 1 and 2 Figure 2 and Figure 4 From the Raman graph, it can be seen that under a pressure of 10 GPa and a temperature of 1800°C, the graphite raw material is completely transformed into diamond in an atmosphere of hydrogen and water, while in Example 3 Figure 6 The Raman diagram shows that the graphite raw material has not been transformed into diamond. Figure 7 and Figure 8 The scanning electron microscope photos show that the synthesized polycrystalline diamond material is relatively dense and has no pores or cracks.

[0044] It can be seen from Examples 1 to 2 that under the catalytic action of hydrogen and water, graphite can be converted into polycrystalline diamond at 10 GPa and 1800°C.

[0045] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A method for catalytically preparing polycrystalline diamond, characterized in that: The method comprises the following steps: putting graphite and a catalyst into a tantalum capsule for encapsulation, then pressing the encapsulated tantalum capsule into a block and putting it into a synthesis cavity for high-temperature and high-pressure synthesis, naturally cooling to room temperature after the synthesis is completed, and obtaining polycrystalline diamond after pressure relief; the conditions of the high-temperature and high-pressure synthesis are as follows: the synthesis pressure is 10 GPa, the synthesis temperature is 1800°C, the heat preservation and pressure holding time is 10 minutes, and the catalyst is ammonia borane or calcium hydroxide.

2. The method for preparing polycrystalline diamond by catalysis according to claim 1, characterized in that: The graphite has a particle size of 1-10 μm.

3. The method for preparing polycrystalline diamond by catalysis according to claim 1, characterized in that: After the pressed tantalum capsule is loaded into the synthesis cavity, the synthesis cavity is heated by an energized rhenium tube, magnesium oxide is used as the pressure transmission medium, and the tantalum capsule is protected by hexagonal boron nitride, and then high-temperature and high-pressure synthesis is carried out.

4. The method for preparing polycrystalline diamond by catalysis according to claim 1, characterized in that: The tantalum capsule obtained after the briquetting is cylindrical.